A randomized, double-blind, Phase 1, single- and multiple-dose placebo-controlled study of the safety and pharmacokinetics of IN-006, an inhaled antibody treatment for COVID-19 in healthy volunteersResearch in context - Thomas R. Moench; Lakshmi Botta; Brian Farrer; Jason D. Lickliter; Hyunah Kang; Yoona Park; Cheolmin Kim; Marshall Hoke; Miles Brennan; Morgan D. McSweeney; Zachary Richardson; John B. Whelan; et al. (EBioMedicine)
Summary: Background: Although COVID-19 is predominantly a respiratory tract infection, current antibody treatments are administered by systemic dosing. We hypothesize that inhaled delivery of a monoclonal antibody may be a more effective and convenient route. We investigated the safety, tolerability, and pharmacokinetics of IN-006, a reformulation of regdanvimab for nebulized delivery by a handheld nebulizer. Methods: A Phase 1 study was conducted in healthy volunteers aged 18–55 a Phase 1 unit in Melbourne, Australia (ACTRN12621001235897). Study staff and participants were blinded to treatment assignment, except for pharmacy staff preparing the study drug. The ratio of active:placebo randomization to each cohort was set at 3:1. The primary outcomes were safety and tolerability. Exploratory outcomes were pharmacokinetics of IN-006 in nasal fluid and serum. Findings: Twenty-three participants were enrolled and randomized across two single dose and one multiple dose cohorts (30 mg or 90 mg single nebulized dose, or seven daily 90 mg doses). There were no serious adverse events. All enrolled participants completed the study without treatment interruption or discontinuation. All treatment-emergent adverse events were transient, non-dose dependent, and graded mild to moderate in severity. Nebulization was well-tolerated and completed in an average of 6 min. Geometric mean nasal fluid concentrations of IN-006 in the multiple dose cohort were 739.8 μg/mL at 30 min after dosing and 1.2 μg/mL at 22 h. Geometric mean serum levels in the multiple dose cohort peaked at 0.51 μg/mL 3 days after the final dose. Interpretation: IN-006 was well-tolerated and achieved concentrations in the respiratory tract orders of magnitude above the IC50 range typical of antiviral mAbs. These data support further development of nebulized delivery of antiviral mAbs for respiratory infectious disease. Funding: This work was funded by the U.S. Army Medical Research and Development Command (W81XWH-15-9-0001) and regdanvimab was provided by Celltrion, Inc.